How can cities learn from each other? Evidence from China's five-year plans - Ying Xu; Eric J. Heikkila (Journal of Urban Management, 2020)
International organizations such as the United Nations, the World Bank, the Organization for Economic Cooperation and Development, and the International Monetary Fund routinely organize cross-learning programs on specific topics for their member governments. Likewise, many national governments organize offers little theoretical or practical guidance on how best to organize such cross-learning activities. One fundamental question is whether to proceed on the basis of cohort- or task-oriented programs, where a cohort-based approach would emphasize shared, institutionalized learning over time amongst local governments with shared planning priorities. To assess this question, we use a case study comparing 286 cities and their avowed priorities for China's 11th and 12th Five-Year Plans. The evidence from our case study supports a task-rather than a cohort-oriented approach. Moreover, because of China's unique administrative structure, with an integrated approach entailing proactive national level guidance and directives, we conclude that for most other countries a cohort-oriented approach would be even less effective. The practical implication of these results is that a task-oriented approach to cross-learning is more advisable.
Keywords: 710; Institutional learning; Issue-based clustering approach; Cross-learning; Five-year plan; Chinese cities